WRITING A LINUX VIRUS WITH LKM - Abdullah, Nada (Iraqi Journal of Science, 2024)
Virus is a program which is able to replicate with little or no user intervention,and the replicated program(s) are able to replicate further. Writing a good virus ischallenging, the best viruses are written in C language, and building as executablefile from C source code to plant virus code into another executable. The result eitherprohibitively large, or very dependent on the completeness of the target installation.Real viruses approach the problem from the other end. They are aggressivelyoptimized for code size and do only what’s absolutely necessary. However, this hassome limitations and the solution to these limitations is complicated and makes thevirus more likely to fail. This paper presents a design and implementation of a virusrunning on Linux operating system as Loadable kernel module (LKM) to overcomethe limitations of developing the virus as C program. This virus can infect Linuxmodules in addition to executable files.